Islam and Prejudice: Special Reference to Gordon W. Allport’s Contact Hypothesis (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This study explores the Muslim perspective on human interaction, relationships and prejudice. A survey of the literature recognises Islam’s fundamental acknowledgement of human diversity, drawing on a dynamic theological, moral, spiritual and legal philosophy revolving around the preservation and sustainment of non-prejudiced human contact. This study discusses the Muslim perspective of human contact, non-prejudice, and accordingly, revisits Gordon W. Allport’s “Theory of Contact Hypothesis” in an effort to compare and contrast it with the Muslim perspective on related issues such as racial prejudice, gender inequity, age prejudice, disability discrimination, social status and classism. This research concludes that Islam has developed a framework necessary for cultivating religiosity and morality without risking the value of effective and harmonious human relations. Further empirical studies on the interplay between Muslim theory and practice on contact hypothesis and prejudice are required to further interpret the dynamics of Muslim values in working settings, and the viability of translating religious ideals into reality.